Miniaturized extracorporeal circulation versus off-pump coronary artery bypass grafting: A meta-analysis of randomized controlled trials. (February 2015) - Benedetto, Umberto; Ng, Colin; Frati, Giacomo; Biondi-Zoccai, Giuseppe; Vitulli, Piergiusto; Zeinah, Mohamed; Raja, Shahzad G.; ,
Abstract: Background: Controversies exist whether off-pump coronary artery bypass (OPCAB) is superior to miniaturized extracorporeal circulation (MECC) in reducing deleterious effects of cardiopulmonary bypass as only a number of smaller randomized controlled trials (RCT) currently provide a limited evidence base. The main purpose of conducting the present meta-analysis was to overcome the expected low power in RCTs in an attempt to establish whether MECC is comparable to OPCAB. Methods: A MEDLINE/PubMed search was conducted to identify eligible RCTs. A pooled summary effect estimate was calculated by means of Mantel-Haenszel method. Results: The search yielded 7 RCTs included in this meta-analysis enrolling 271 patients in the OPCAB group and 279 in the MECC group. The OPCAB and MECC groups were comparable in terms of incidence of in-hospital mortality (Risk Difference [RD] 0.01; 95%CI −0.02, 0.03; P = 0.55; I 2  = 0%), stroke (RD −0.01; 95%CI −0.05, 0.04; P = 0.69; I 2  = 0%), need for renal replacement therapy (RD 0.00; −0.06, 0.06; P = 1; I 2  = 0%), postoperative atrial fibrillation (RD −0.03; −0.17, 0.10; P = 0.64; I 2  = 0%), re-exploration for bleeding (RD −0.01; 95%CI −0.03, 0.02; P = 0.65; I 2  = 0%), transfusion rate (RD −0.01; 95%CI −0.03, 0.02; P = 0.65; I 2  = 0%) and the amount of blood loss (weighted mean difference -25 mL; 95%CI −71, 21; P = 0.28; I 2  = 0%). Conclusions: Using a meta-analytic approach, MECC achieves clinical results comparable to OPCAB including postoperative blood loss and blood transfusion requirement. On the basis of our findings, MECC should be considered as a valid alternative to OPCAB in order to reduce surgical morbidity of conventional cardiopulmonary bypass. Highlights: Superiority of OPCAB over MECC in reducing CPB-related side-effects is controversial. This controversy is due to current available evidence from limited number of small-sized randomised controlled trials. Present meta-analysis confirms that MECC has clinical outcomes comparable to OPCAB. MECC should be considered as a valid alternative to OPCAB in order to reduce CPB-related morbidity.